Implementación contable en la estación de servicios Lagoriente en la ciudad de Nueva Loja, periodo septiembre 2013 - Catota Rojas, Monica Lucia (2014)
The accounting implementation LAGORIENTE service station in the city of Nueva Loja, September 2013 period "will help the owner knows the record of economic and financial transactions in the accounting records in accordance with the provisions of the rules and principles of generally accepted accounting process and obtain reliable, comparable and relevant to decision making that will improve the profitability of the petrol Financial Statements. Pursuant to the objectives proceeded to the collection of documents such as invoices, withholding, checks among others that allowed information to prepare the memorandum of operations, then the plan and manual accounts agreement was drawn to the need Gasoline requires the control of the Merchandise has it performed by the system account or multiple periodic inventory, the accounting process is executed in the Service Station Lagoriente starting with the inventory to obtain the financial statements. Final concludes that delivered a systematically arranged according to International Accounting Standards accounting process, which is encouraged to consider the information obtained to help them make investment decisions.